Religiosidade e qualidade de vida em idosos institucionalizados - Carneiro, Licania Correia (2009)
This is a research of transversal and observational character aiming to evaluate the religiosity influence in the Life Quality of Institutionalized Elderly People. The sample involved 78 subjects, in six institutions of long permanence from Catholic origin, in the city of João Pessoa/PB. The analyzed methodology focused on quantified data obtained through the fulfillment of two (02) instruments: the Religious Attitude Scale which investigates the religious level by means of knowledge, behavior, emotions and religious conceptions, and the generic instrument of life quality evaluation, known as SF-36, with domains in functional capacity, physical aspects, pain, general health state, vitality, social aspects, emotional aspects and mental health. The religious attitude ranged from low to high taking into account the mean which divides the sample into two parts. The statistical analysis used tools from the descriptive statistics with the SPSS (Statistical Package for the Social Science) for Windows. Mean calculi and standard deviation were used to attain the value knowledge of the items of the Religious Attitude Scale, from Pearson correlation, in order to verify associations among the variables, and an analysis of the variance (ANOVA) with t test to identify where occurred the differences in the average of life quality domains due to low and high religiosity. The results showed correlation between the religious attitude and life quality in mental health (p= 0,05), vitality (p= 0,05) and general health state (p= 0,002). It can be concluded that the religiosity influence concerning life quality of institutionalized elderly constitutes an important factor regarding health state of such individuals.